Antimicrobial resistance patterns of bacterial pathogens recovered from the urine of patients at Canadian hospitals from 2009 to 2020. Issue 6 (30th November 2022) - Walkty, Andrew; Karlowsky, James A; Lagace-Wiens, Philippe; Baxter, Melanie R; Adam, Heather J; Zhanel, George G
Abstract: Objectives: To investigate in vitro susceptibility patterns of bacterial pathogens recovered from the urine of outpatients (isolates from outpatient clinics or emergency departments) and hospital inpatients across Canada from 2009 to 2020 as part of the CANWARD study Methods: Canadian hospital microbiology laboratories submitted bacterial pathogens cultured from urine to the CANWARD study coordinating laboratory on an annual basis (January 2009 to December 2020). Antimicrobial susceptibility testing was performed by CLSI broth microdilution, with MICs interpreted by current CLSI breakpoints. Results: In total, 4644 urinary pathogens were included in this study. Escherichia coli was recovered most frequently (53.3% of all isolates), followed by Enterococcus faecalis, Klebsiella pneumoniae, Proteus mirabilis, Pseudomonas aeruginosa and Staphylococcus aureus . Together, these six species accounted for 84.2% of study isolates. Nitrofurantoin demonstrated excellent in vitro activity versus E. coli, with 97.6% of outpatient and 96.1% of inpatient isolates remaining susceptible. In contrast, E. coli susceptibility rates were lower for ciprofloxacin (outpatient 79.5%, inpatient 65.9%) and trimethoprim/sulfamethoxazole (outpatient 75.2%, inpatient 73.5%). The percentage of E. coli isolates that were phenotypically positive for ESBL production significantly increased from 4.2% (2009–11) to 11.3% (2018–20). A similar although less pronounced temporal trend was observed with ESBL-producing K. pneumoniae . Conclusions: E. coli was the pathogen most frequently recovered from the urine of Canadian patients, and the proportion of isolates that were ESBL producers increased over time. Susceptibility data presented here suggest that ciprofloxacin and trimethoprim/sulfamethoxazole may be suboptimal for the empirical treatment of complicated urinary infections.